2010
DOI: 10.1108/13612021011025492
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chinese and Indian consumers' evaluative criteria when selecting denim jeans

Abstract: PurposeUS apparel firms have been relatively slow exploring Chinese and Indian apparel markets, despite the countries' tremendous growth potentials. To help US apparel firms successfully enter these promising markets, this study aims to compare evaluative attributes that Chinese and Indian consumers utilize when purchasing denim jeans.Design/methodology/approachData were collected in Shanghai, China and Bangalore, India.FindingsThe results of the study confirmed that Chinese and Indian consumers ranked attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 31 publications
3
55
0
3
Order By: Relevance
“…Several cross-cultural studies (Dawar and Parker, 1994;Moon, Chadee, and Tikoo, 2008;Noh and Seo, 2009) have suggested that product attributes may influence consumers' purchase intentions differently depending on consumers' nationality and other characteristics such as culture and lifestyle (Shawn, 1994;Wee, 1999;Chen-Yu, Hong, & Seock, 2010;Jin, Park, & Ryu, 2009). Hsu and Burns (2002) find that American female college students consider comfort, size and fit and quality to be more important in determining whether to purchase clothing than Taiwanese female college students.…”
Section: Introductionmentioning
confidence: 97%
“…Several cross-cultural studies (Dawar and Parker, 1994;Moon, Chadee, and Tikoo, 2008;Noh and Seo, 2009) have suggested that product attributes may influence consumers' purchase intentions differently depending on consumers' nationality and other characteristics such as culture and lifestyle (Shawn, 1994;Wee, 1999;Chen-Yu, Hong, & Seock, 2010;Jin, Park, & Ryu, 2009). Hsu and Burns (2002) find that American female college students consider comfort, size and fit and quality to be more important in determining whether to purchase clothing than Taiwanese female college students.…”
Section: Introductionmentioning
confidence: 97%
“…For luxury brands, high price and excellent quality go together as inherent traits (Shukla 2012). Prior studies have observed that functional value, and especially price-quality perceptions, plays a significant role in value formation for inconspicuous products for the Chinese (Jin et al 2010), and for luxury goods amongst Indian (Shukla 2012) and Indonesian consumers (Rao 2005 A survey of actual luxury consumers was used to test the hypotheses. First, a questionnaire was developed based on existing scales.…”
Section: Functional Valuementioning
confidence: 99%
“…For instance, Christodoulides et al (2009) concluded that Taiwanese consumers are less likely to consume a luxury brand owing to its perceived uniqueness or ability to shape self-concept, because Taiwan as a society stresses collectivism and avoids uncertainty. By reviewing their fi ndings with Jin et al (2010) , Lu (2008) and Yau ' s (1988) research on Chinese consumers, Hofstede's (1998Hofstede's ( , 2001 cultural dimensions are useful in this study ' s context.…”
Section: Introductionmentioning
confidence: 97%